2012
DOI: 10.5539/jas.v4n12p27
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Salt Tolerance of 14 Barley Accessions from Southern Tunisia Using Multiple Parameters

Abstract: Barley "Ardhaoui" (Hordeum vulgare L.) is a local landraces cropped in southern Tunisia characterized by its resistance to drought and salinity. Salt tolerance of barley changes according to the growth stages. In order to study the salinity tolerance of (Hordeum vulgare L.), fourteen barely accessions, were grown in soil and exposed to four salinity levels (5, 7, 13 and 20 dS/m).To evaluate its salt tolerance using multiple parameters, fourteen barley accessions from two regions in the southern Tunisia (costal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…However, the most tolerant ones showed minimal percentages decrease. These results corroborate those obtained by Ben Khaled et al (2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the most tolerant ones showed minimal percentages decrease. These results corroborate those obtained by Ben Khaled et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…However, within barley, the most sensitive stages towards salinity seem to be the earlier growth stages (Adjel et al 2013). Indeed, the vegetative stage which is characterized by its high tillering capacity appears to be a very important stage to evaluate genotypes response towards salinity (Ben Khaled et al 2012). Thus salt tolerance at vegetative stage is considered as an important indicator of barley salt tolerance at later growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…In southern Tunisia, where precipitation is very low, barley is the predominant cereal due to its tolerance to drought stress. In this region, there are many landraces, such as those included in the “Ardhaoui”, “Beldi”, “Djebali”, “Djerbi”, “Frigui”, “Sfira” or “Souihlis” landrace groups, which are well-known for their stress tolerance [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that crop landraces are generally well adapted to the agroclimatic conditions of the region where they evolved and may contain a large genetic variation [ 24 ], they represent an interesting source for the selection of drought-tolerant materials. Barley landraces from Tunisia are genetically variable [ 18 , 25 ] and therefore are amenable to selection for drought tolerance, as long as diversity exists for this trait. In this respect, Ben Khaled et al [ 18 , 26 ] found genetic variation for salinity tolerance among different landrace accessions of the “Ardhaoui” barley, which is autochthonous of southern Tunisia and is grown in areas with low precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a characterization based on the vegetative, yield and its related traits was investigated, which showed a high intra-specific diversity among the North African genotypes regarding salt tolerance. The existence of a large amount of genetic diversity has been already reported on barley (Royo and Aragues, 1999;Ben Khaled et al, 2012), rice (Mahmood et al, 2009) and wheat (El-Hendawy et al, 2005).…”
Section: Discussionmentioning
confidence: 86%